Au-In-based hermetic sealing for MEMS packaging for down-hole application - Vivek, Chidambaram (2014)
Hermetic sealing of micro-electro mechanical systems (MEMS) sensors for down-hole application requires high-quality void-free bonds, with metallic hermetic sealing being widely used for this purpose. As most of the MEMS sensors cannot withstand high temperatures, transient liquid phase (TLP) bonding is promising for metallic sealing applications, since the re-melting temperature of the bond is much higher than the bonding temperature. In this paper, major issues involving TLP bonding, including non-uniform diffusion kinetics across the interface and the formation of intermetallic compounds prior to bonding for fast reactive metallic systems like Au-In, have been addressed by using diffusion barriers. The performance of various diffusion barriers that include Ti, Ni, and Pt has been evaluated. Ni has been determined to be a prospective candidate, since it averts diffusion to a certain extent prior to TLP bonding. The mechanical strength and hermeticity of the Au-In joints have also been characterized after aging at 300 °C up to 500 h. No major changes in the thermo-mechanical properties of the AuIn and AuIn2 phases were observed and, hence, these phases are concluded to be thermally stable at this temperature regime. Improvements in hermeticity were confirmed when subjected to high-temperature thermal aging.